(untitled) (Comparative Professional Pedagogy, 2024)
Foreign experience regarding the prioritized technologies of digital education and their integration into the educational process of German universities is analyzed in the article. It is discovered that digital education is dynamic and promising and is based on the humanistic image of the person, scientific accessibility, the ability of critical reflection and relevant scientific practice. Besides, further purposeful learning of didactics by lecturers in higher educational institutions contributes to the sustainable improvement of teaching quality. It is found that generative artificial intelligence is increasingly becoming a powerful tool for various forms of achievements validation. The learning analytics and the importance of students’ social integration in the digitalization process are analyzed. It is established that the basic ethical understanding of working with generative artificial intelligence includes accountability, responsibility and transparency. The characteristic features of an artificial intelligence system are autonomy, interactivity and adaptability. It is found that using chatbots based on artificial intelligence in the educational process is only partially beneficial for the applied orientation of teaching at the university. In the context of digital education at Siegen University, the combined structure of the implemented categories regarding to the support and development of specific proposals in the teaching and learning process is analyzed. The relevance of the issue concerning the support of lecturers, their didactic concepts and purposeful methods for teaching enrichment with the help of digital tools and infrastructure is highlighted. According to the results of the foreign experience study, it is found that all proposals that were developed from the position of the combined didactic and technical perspectives meet the objectives regarding the quality of student-oriented and competence-oriented education. It is concluded that generative intelligence technologies are priority. An important didactic aspect in the context of digitalization is an integrative approach towards digital transformation in the universities of Germany.